2010
DOI: 10.1161/circulationaha.109.892414
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphodiesterase Inhibitor Cilostazol Induces Regression of Carotid Atherosclerosis in Subjects With Type 2 Diabetes Mellitus

Abstract: Background-Antiplatelet drugs are effective in preventing recurrence of atherosclerosis in type 2 diabetic patients.However, the efficacy and usefulness of 2 different antiplatelet drugs, aspirin and cilostazol, in the progression of carotid intima-media thickening are unknown. 001).In a regression analysis adjusted for possible confounding factors such as lipid levels and hemoglobin A 1c , the improvements in common carotid artery intima-media thickness with cilostazol treatment over aspirin treatment remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 31 publications
(28 reference statements)
4
80
0
4
Order By: Relevance
“…Therefore, a total of 642 subjects can provide a minimum of 80% power at a 2-sided significance level of 0.05 to detect a significant difference in the event rates between the 2 groups. Multicenter study group B: Based on data reported by Katakami, et al, 14) the estimated difference in the progression of meanIMT at 3 years between the subjects within the fourth quartile range of FMD values and those within the first quartile range of FMD values is 0.04 mm. The population size is considered to provide adequate power to test the hypothesis that the progression of the meanIMT of the subjects within the fourth quartile range of FMD values is lower than that of the subjects within the first quartile range of FMD values.…”
Section: Population Sizesmentioning
confidence: 99%
“…Therefore, a total of 642 subjects can provide a minimum of 80% power at a 2-sided significance level of 0.05 to detect a significant difference in the event rates between the 2 groups. Multicenter study group B: Based on data reported by Katakami, et al, 14) the estimated difference in the progression of meanIMT at 3 years between the subjects within the fourth quartile range of FMD values and those within the first quartile range of FMD values is 0.04 mm. The population size is considered to provide adequate power to test the hypothesis that the progression of the meanIMT of the subjects within the fourth quartile range of FMD values is lower than that of the subjects within the first quartile range of FMD values.…”
Section: Population Sizesmentioning
confidence: 99%
“…These three determinations were averaged (mean CCAIMT). 33 Mean CCAIMT was determined on both the left and right sides, and the larger value was used for analyses. 14 …”
Section: Mri Assessmentmentioning
confidence: 99%
“…2010 yılında yayımlanan, silostazol tedavisinin Tip 2 diabetes mellituslu hastalarda karotis aterosklerozuna etkilerini inceleyen çalışmalarında, silostazol tedavisi uygulanmış hastalarda LDL kolesterol değerlerinde başlangıç değerlerine göre anlamlı bir iyileşme saptadıklarını (117±33 mg/dL'den 109± 31 mg/dL'ye, p=0,009) fakat ASA uyguladıkları hastalarda LDL kolesterol değerlerindeki iyileşmenin başlangıç değerlerine kıyasla önemli ölçüde olmadığını (p=0,054) saptadıklarını bildirmişlerdir. 17 Bizim çalışmamızda da karotis arter stenozu medikal tedavisi nedeni ile silostazol kullanan hastalarda LDL kolesterol değer-lerindeki iyileşmenin (p=0,000) ASA+pentoksifilin kullanan hastalarınkine oranla daha fazla olduğu saptanmıştır.…”
Section: Ica-stenozunclassified
“…17 Bizim çalışmamızın sonuçlarında da silostazol tedavisi kullanan hastaların ICA-İMK değerlerindeki baş-langıç değerlerine göre iyileşmenin (0,94±0,25 mm'den 0,82±0,14 mm'ye, p=0,009) ASA+pentok-sifilin tedavisi kullanan hastalardaki iyileşmeden (0,91±0,25 mm'den 0,89±0,22 mm'ye, p=0,924) orantısal ve istatistiksel olarak anlamlı şekilde daha fazla olduğu saptanmıştır.…”
Section: Ica-stenozunclassified